Impact resistance of concrete and fibre-reinforced concrete: A review - Esaker, Mohamed; Thermou, Georgia E.; Neves, Luis (International journal of impact engineering, 2023)
•This paper summarises the research carried out to date on the impact resistance of concrete subjected to different impact load regimes, with a focus on high-velocity projectile impact load.•An experimental database is compiled on the response of concrete elements to high-speed projectile impacts, which is used to identify the critical failure modes of concrete under impact loads (i.e. spalling, scabbing, penetration, and perforation of the targeted specimens) and the parameters influencing the impact resistance of concrete (i.e. velocity, mass and shape of the projectile, concrete compressive strength, type and size of aggregate, and type and ratio of reinforcement).•In addition, the adequacy of existing empirical formulas to predict the penetration depth is assessed by using the experimental database.•A critical discussion highlights the effect of various design parameters on the impact resistance of concrete and determines the key aspects that should be addressed in future research. This paper summarises the research carried out to date on the impact resistance of concrete subjected to different impact load regimes, with a focus on high-velocity projectile impact load. An experimental database is compiled on the response of concrete elements to high-speed projectile impacts, which is used to identify the critical failure modes of concrete under impact loads (i.e. spalling, scabbing, penetration, and perforation of the targeted specimens) and the parameters influencing the impact resistance of concrete (i.e. velocity, mass and shape of the projectile, concrete compressive strength, type and size of aggregate, and type and ratio of reinforcement). In addition, the adequacy of existing empirical formulas to predict the penetration depth is assessed by using the experimental database. A critical discussion highlights the effect of various design parameters on the impact resistance of concrete and determines the key aspects that should be addressed in future research.